2020
DOI: 10.1038/s41588-020-00722-w
|View full text |Cite
|
Sign up to set email alerts
|

Triticum population sequencing provides insights into wheat adaptation

Abstract: Bread wheat expanded its habitats from a small core area of the Fertile Crescent to global environments within ~10,000 years. Genetic mechanisms of this remarkable evolutionary success are not well understood. By whole-genome sequencing of populations from 25 subspecies within genera Triticum and Aegilops, we identified composite introgression from these wild populations contributing 13%~36% of the bread wheat genome, which tremendously increased the genetic diversity of bread wheat and allowed its divergent a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
301
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(318 citation statements)
references
References 79 publications
14
301
2
1
Order By: Relevance
“…Moreover, LD-based maps are representative of a whole population and less susceptible to individual specific variation, for example introgressions which are known to prevent local formation of CO between the introgressed chromatid and the native chromatid. Introgressions from wild relative species are frequent in bread wheat species, representing from 4 to 32% of bread wheat genome (Zhou et al 2020). The limitation of LD-based maps relies on the fact that they can be affected by evolutionary patterns, which in turn can hinder their usefulness to study the evolution of recombination rate.…”
Section: Ld-based Recombination Maps Correlate Well With the Biparentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, LD-based maps are representative of a whole population and less susceptible to individual specific variation, for example introgressions which are known to prevent local formation of CO between the introgressed chromatid and the native chromatid. Introgressions from wild relative species are frequent in bread wheat species, representing from 4 to 32% of bread wheat genome (Zhou et al 2020). The limitation of LD-based maps relies on the fact that they can be affected by evolutionary patterns, which in turn can hinder their usefulness to study the evolution of recombination rate.…”
Section: Ld-based Recombination Maps Correlate Well With the Biparentmentioning
confidence: 99%
“…These introgressions repress recombination (Worland et al 1988) and this resulted in a poor correlation between CsRe genetic map and our LD-based maps for genomic region 7DR3 in our analysis. It was recently shown that natural or artificial introgressions of wheat wild-relatives DNA contributed to up to 710 Mb and 1580 Mb in wheat landraces and varieties respectively (Cheng et al 2019), and represent from 4 to 32% of bread wheat varieties genome (Zhou et al 2020). A similar analysis used exome capture to evaluate introgression in 890 hexaploid and tetraploid wheats (He et al 2019).…”
Section: Evolution Of the Recombination Landscape In Bread Wheatmentioning
confidence: 99%
“…S2). These separate lineages were also observed in the phylogenetic analysis based on RNA-seq-based polymorphisms [34] and whole-genome polymorphisms in wild einkorn [36]. The habitats of L1 accessions were southern Turkey, northern Iraq, and Iran, which correspond to the Fertile Crescent.…”
Section: Discussionmentioning
confidence: 61%
“…Wheat (Triticum aestivum L.) is the most-extensively cultivated staple crop (~ 17% of the total cultivated area) in the world 1 . It serves as a leading food for human consumption as an essential source of starch, proteins, vitamins, dietary ber, and phytochemicals 2 .…”
Section: Read Full License Introductionmentioning
confidence: 99%